PENGARUH PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAMBI - M Zahari MS (Ekonomis: Journal of Economics and Business, 2017)
Positive economic growth indicates an increase in the economy of a country or region, whereas negative economic growth indicates a decline in the economy of a country or region. The indicator used to measure regional economic growth is the growth rate of Gross Regional Domestic Product at constant prices (real GDP). In increasing the economic growth of a region, not apart from the role of government in providing funds to finance regional economic development activities. Costs incurred for public service activities and development both economic and non-economic are often referred to as government expenditures. These government expenditures are allocated annually in the Regional Revenue and Expenditure Budget. Excavation of potential sources of income to support local expenditure and regional independence needs to be intensified, especially those originating from local revenue sources optimally will be able to contribute significantly to the improvement of Jambi Province's Regional Income and Expenditure Budget. The purpose of this study is to determine the financial capacity of regions derived from local revenue in supporting the Regional Revenue and Expenditure Budget, and to determine the rate of regional economic growth and analyze the influence of regional spending on economic growth in Jambi Province. This research was conducted in the scope of government of Jambi Province. The research method used qualitative descriptive method and linear regression analysis of econometric model of Ordinary Least Square method (OLS). The results show that during the period from 2010 to 2016, the financial capacity of regions originating from local own revenues has not been fully reliable in sustaining the Jambi Provincial Revenue and Expenditure Budget, as its contribution is still relatively low at an average of 34.13 percent per year . The economic growth of Jambi Province during the same period grew by 6.28 percent per year. Government expenditures significantly and positively affect the Economic Growth of Jambi Province. The conclusion is that an increased regional government spending will lead to increased economic growth of the region concerned.Keywords: Regional Finance, Government Expenditure, Economic Growth.